2019
DOI: 10.48550/arxiv.1911.09867
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Full Characterization of Minimal Linear Codes as Cutting Blocking Sets

Abstract: In this paper, we first study more in detail the relationship between minimal linear codes and cutting blocking sets, which were recently introduced by Bonini and Borello, and then completely characterize minimal linear codes as cutting blocking sets. As a direct result, minimal projective codes of dimension 3 and t-fold blocking sets with t ≥ 2 in projective planes are identical objects. Some bounds on the parameters of minimal codes are derived from this characterization. Using this new link between minimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…Finally, in all our constructions of minimal codes, and in other constructions provided in [8,9,12,36], we observed that the minimum distance satisfies d ≥ (k − 1)(q − 1) + 1, where this bound is met with equality in all our constructions of reduced minimal codes. Therefore, also motivated by Remark 4.4, where we observed that the bound of Theorem 4.3 is not sharp, we propose the following conjecture.…”
Section: Conclusion and Open Problemssupporting
confidence: 59%
“…Finally, in all our constructions of minimal codes, and in other constructions provided in [8,9,12,36], we observed that the minimum distance satisfies d ≥ (k − 1)(q − 1) + 1, where this bound is met with equality in all our constructions of reduced minimal codes. Therefore, also motivated by Remark 4.4, where we observed that the bound of Theorem 4.3 is not sharp, we propose the following conjecture.…”
Section: Conclusion and Open Problemssupporting
confidence: 59%
“…The previous bound is not tight in general. More precisely, in [1] it was conjectured (and then proved in [32]) that the length n of an [n, k] q minimal code satisfies the following lower bound.…”
Section: Minimal Codesmentioning
confidence: 99%
“…The concept of a cutting blocking set was introduced in [13] for constructing a family of minimal codes. In [1] and [32] it was independently shown that cutting blocking sets are in one to one correspondence with minimal linear codes. In this subsection, we recall some properties of (cutting) blocking sets and known results about their size.…”
Section: Minimal Codes and Cutting Blocking Setsmentioning
confidence: 99%
See 2 more Smart Citations